The Use of lithium in psychiatric, viral and neurological disorders - a review - Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika (Journal of Education, Health and Sport, 2023)
Introduction: Lithium is one of the longest used drugs in psychiatry and is currently a mainstay in the long-term prophylaxis of bipolar disorder, preventing recurrent manic and depressive episodes. It also remains an important drug in the treatment of acute episodes of mania and depression. Out of the normothymic drugs, lithium has the greatest effect in preventing suicidal behavior. It also exhibits antiviral activity and in recent years evidence has also accumulated of the drug's neuroprotective properties. Aim of the study: The aim was to collect and analyze publications on the use of lithium in affective disorders, dementia and viral diseases, as well as its effect on reducing suicidal tendencies. Materials and Methods: The literature available in the PubMed database was reviewed, using the key words: "lithium"; "bipolar disorder"; "mania", "depression"; "suicidal risk", "side effects". Results: Chronic use of lithium in patients with bipolar disorder has an effect on preventing recurrence of manic and depressive episodes and can successfully last for 40 years or longer. Studies support the theory that long-term lithium pharmacotherapy has a significant impact on preventing suicidal tendencies among patients with affective disorders. In recent years, the antiviral and neuroprotective properties of the drug have also become known. Despite the rather high risk of overdose, as well as the occurrence of numerous side effects, lithium is still very often used in the treatment of affective disorders due to its high efficacy. Conclusions: Lithium has been one of the mainstays of psychopharmacology for several decades and is a precursor to mood-stabilizing drugs. In recent years evidence has also been collected for its potential use in non-psychiatric conditions. Conducting further research on lithium will certainly allow for wider use of the drug and a more thorough understanding of its mechanism of action.